"Cataluna como un estado" Rozważania wokół secesji Katalonii = "Cataluna como un estado" Considerations about the secession of Catalonia - Husar, Wioletta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article takes the issue of a possible secession of catalonia into consideration. Its main objective is to identify factors that contribute to and hinder the aforementioned autonomous community from becoming independent. The implementation of this task is to isolate the specific features of the region and its people that affect the creation of the catalan national identity. The analysis of the possibility of secession was based on three levels: economic, historical-cultural and legal-political. The construction of the balance of profit and loss will allow to adopt a forecast of potential solutions to the problem. The study used statistical data, studies in the literature and source documents.
Keywords: Katalonia; secesja; tożsamość narodowa; nacjonalizm gospodarczy; referendum niepodległościowe